2018
DOI: 10.18632/oncotarget.23827
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of variability of five programmed death ligand-1 immunohistochemistry assays in non-small cell lung cancer samples

Abstract: Programmed death ligand-1 (PD-L1) expression as determined by immunohistochemistry (IHC) is potentially predictive of clinical outcome. The aim of this study was to assess the concordance of reported PD-L1 IHC assays and investigate factors influencing variability. Consecutive sections from 20 non-small cell lung cancers (NSCLCs) comprising resection, core biopsy, cytology and pleural fluid samples underwent IHC with 5 different antibody/autostainer combinations: 22C3/Link48, 28-8/BOND-MAX, E1L3N/BOND-MAX, SP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…[3][4][5][6] Most studies in this field have found that 10% to 20% of cases will be classified differently as above or below clinical cutoffs, depending on the assay used. 3,4,[7][8][9] We agree that our data are "not greatly different from those in the Blueprint Phase 1 study." 1(para.5) However, we could not interpret these data and conclude, as other authors have, that the SP263, 22C3, and 28-8 assays are interchangeable.…”
Section: In Responsesupporting
confidence: 72%
“…[3][4][5][6] Most studies in this field have found that 10% to 20% of cases will be classified differently as above or below clinical cutoffs, depending on the assay used. 3,4,[7][8][9] We agree that our data are "not greatly different from those in the Blueprint Phase 1 study." 1(para.5) However, we could not interpret these data and conclude, as other authors have, that the SP263, 22C3, and 28-8 assays are interchangeable.…”
Section: In Responsesupporting
confidence: 72%
“…Taking the CAP guidelines into account this does not support the conclusion from the authors of ‘analytical evidence for interchangeability of the 22C3, 28‐8 and SP263 assays’. Remarkably, other studies reported that SP263 had higher PD‐L1 scores than 22C3 in several cases or low correlation between these two assays , while Kim and colleagues show more positive cases in 22C3 than in SP263 . Interestingly, when looking at individual cases around the threshold of 1% PD‐L1 positivity, comparison of 22C3 with SP263 shows in some cases higher staining for SP263 and in other cases higher for 22C3 .…”
Section: Discussionmentioning
confidence: 86%
“…Details on the used antibodies, antibody retrieval procedures, and OPAL dyes are given in Table 1. The experimental procedure was performed according to the manufacturer's instructions [23]. Slides were initially boiled in a microwave (15 minutes at 100°C) for antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%